Evaluation of 2-acetyl-1-pyrroline in foods, with an emphasis on rice flavour. (1st October 2017) - Wei, Xuan; Handoko, Dody D.; Pather, Leela; Methven, Lisa; Elmore, J. Stephen
Highlights: 2-Acetyl-1-pyrroline (2-AP) is a key contributor to the aroma of fragrant rice. It can be formed enzymatically in the grain and also chemically when rice is heated. This review examines the formation of 2-AP, its synthesis, stabilisation and analysis. Abstract: The popcorn-like aroma compound 2-acetyl-1-pyrroline (2-AP) is a key contributor to the desirable aroma of fragrant rice and is also important in the aroma of other foods, such as pandan leaf, popcorn and Mediterranean sausage. It can be formed enzymatically in the rice grain as it grows and is also formed, as part of the Maillard reaction, when rice is heated. This review examines the formation of 2-AP in rice and other foods, particularly its formation during cooking, focusing on the importance of the Maillard reaction between reducing sugar breakdown products and 1-pyrroline derived from the amino acids proline and ornithine. The synthesis of 2-AP is discussed alongside the attempts that have been made to stabilise this relatively unstable compound. The analysis of 2-AP by instrumental techniques, particularly gas chromatography-mass spectrometry and gas chromatography-olfactometry, alongside the use of sensory studies, is also discussed.